CST315 - Principles of Parallel & Distributed Programming - March 2005 - PPSKOM, Pusat Pengajian Sains Komputer (2005)
UNIVERSITI SAINS MALAYSIA Second Semester Examination Academic Session 2004/2005 March 2005 CST315 - Principles of Parallel & Distributed Programming Duration : 2 hours